Human Embryonic Stem Cell-Derived Retinal Pigment Epithelium-Role in Dead Cell Clearance and Inflammation. - Szatmári-Tóth Mária; Ilmarinen Tanja; Mikhailova Alexandra; Skottman Heli; Kauppinen Anu; Kristóf Endre; Veréb Zoltán; Fésüs László; Petrovski Goran (2019)
Inefficient removal of dying retinal pigment epithelial (RPE) cells by professional phagocytes can result in debris formation and development of age-related macular degeneration (AMD). Chronic oxidative stress and inflammation play an important role in AMD pathogenesis. Only a few well-established in vitro phagocytosis assay models exist. We propose human embryonic stem cell-derived-RPE cells as a new model for studying RPE cell removal by professional phagocytes. The characteristics of human embryonic stem cells-derived RPE (hESC-RPE) are similar to native RPEs based on their gene and protein expression profile, integrity, and barrier properties or regarding drug transport. However, no data exist about RPE death modalities and how efficiently dying hESC-RPEs are taken upby macrophages, and whether this process triggers an inflammatory responses. This study demonstrates hESC-RPEs can be induced to undergo anoikis or autophagy-associated cell death due to extracellular matrix detachment or serum deprivation and hydrogen-peroxide co-treatment, respectively, similar to primary human RPEs. Dying hESC-RPEs are efficiently engulfed by macrophages which results in high amounts of IL-6 and IL-8 cytokine release. These findings suggest that the clearance of anoikic and autophagy-associated dying hESC-RPEs can be used as a new model for investigating AMD pathogenesis or for testing the in vivo potential of these cells in stem cell therapy.